Ultrasound-Guided Musculocutaneous Nerve Block in Postherpetic Neuralgia. (January 2016) - Kuo, Ying-Chen; Hsieh, Lin-Fen; Chiou, Hong-Jen
Abstract : ABSTRACT: Postherpetic neuralgia is a common and challenging complication of herpes zoster infection, particularly in older people. In recent decades, first-line treatments, including oral or topical medication, have become well established. However, few studies have reported the efficacy of interventional procedures for the treatment of postherpetic neuralgia. Here, the authors present a case of intractable postherpetic neuralgia treated with musculocutaneous peripheral nerve block under ultrasound guidance. Symptoms remained controlled at 1 mo follow-up. Ultrasound can be readily applied to improve the accuracy and efficiency of peripheral nerve block as it is currently widely used to evaluate the musculoskeletal system in clinical settings.